The Turkish Cypriot municipalities' productivity and performance: An application of data envelopment analysis and the Tobit model - Dilber Çağlar (Journal of Risk and Financial Management, 2021)
Nowadays, countries are more concerned with the improvement of effectiveness and efficiency in public sector activities in the perspective of frugal innovation. The problem centers around how to obtain more and better public service with the limitations of the public incomes and indebtedness in preserving environmental conditions. This paper empirically investigates the efficiency, technical efficiency, productivity, and the determinants factor of implementing sustainable development policy of the five major municipalities in North Cyprus by conducting DEA and Tobit analyses during the period from 2004 to 2018 quarterly. The empirical results show that the size of the economically active population of a city, lower expenditures, and grants result in a higher efficiency, whereas the independent revenue sources (grants) and the per capita expenditures of North Cypriot municipalities have a negative effect on the efficiency. The employment rate in the municipalities has a considerable negative effect on the efficiency score. The results of Tobit analysis also show that population has a positive impact which may increase the technical efficiency. Finally, the findings of this study demonstrated that implementing proper environmental programs not only improve the efficiency of local government but also help the ecological sustainability and the geographical location of the regional changes and barriers for sustainable initiatives by using proper waste mechanism, clean water technology, and solar lighting.
Keywords: 330; DEA; ecological sustainability; efficiency; employment; frugal innovations; municipalities; sustainable development; Tobit analysis